Pengaruh intensitas kebisingan tinggi terhadap aktivitas kelenjar tiroid mencit (mus musculus) betina = The Effect of the High Noise Intensity at Thyroid Gland Activity of Female Mice (Mus musculus) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
ABSTRACT Noise is an environmental pollutan. It may disturbs the function of some endocrine glands. The aim of this study is to explore the effect of noise at thyroid and the high f oliculli epithelium cell and body weigth of female mice (Mus musculus). This study using females mice (Mus musculus) which were devided into three groups, i.e. control group, noise induction at 90-94 dB group and noise induction at 100-104 dB, each group consists of ten. During 12 days, the control group was not treatment, except 1 of mice control group was injected with tyroxine hormone for positive control. In the same time the treatment group was inducted was 12 days and 8 haours per day. The nutrition with BRI was given 15-20 g and fresh water 15-30 ml during this treatment. The temperature, humidity and body weigth also measured at this treatmen everyday. In the last day of the treatment induction was ended. The 12th day, the blood was taken for measuring tyroxine hormone and thyroid stimulating hormone. Lastly, the thyroid gland was taken out for the slice of microscopies smear. The results of this study showed that the high intensity of noise increased the activity of the female mice (Mus musculus) thyroid gland. As the shown by increasing of tyroxine hormone, decrease of TSH and low of ratio diameter folicullli and high foliculli epitelium cell for induction 90-94 dB group and 100-104 group. Beside the rate of increasing body weight treatment groups were decreased in comparison for control group.